IMPLEMENTASI GOOD GOVERNANCE PADA LEMBAGA SWADAYA MASYARAKAT (Studi Kasus Pada Aksi Cepat Tanggap Cabang Semarang) - Sektiono, Dwi; Nugraheni, Rini (Faculty of Economics and Business Diponegoro University, 2017)
This research aims to identify, study and understand the organizational management in the non-profit organization Aksi Cepat Tangap Semarang branch with the paradigm of good governance. Using a qualitative case study method with a phenomenon know in depth the various resources required.Aksi Cepat Tanggap committed to become a professional non-profit organization that makes growing rapidly to gained trust society. The results of this study show that the Aksi Cepat Tanggap had been applied the principles of good governance. Conclusion this study found that when a non- profit organization to apply the principles of good governance, non-profit organizations may develop rapidly, lasting and gain public confidence.